Indonesian EFL students’ perceptions of TikTok utilization in EFL learning - Suciani, Ni Ketut; Sanjaya, I Nyoman Suka; Sitawati, Anak Agung Raka; Wariyati, Wariyati (Journal of Applied Studies in Language, 2023)
Despite its increasing popularity among young adults, TikTok has been very slow in finding its way into the English as a foreign language (EFL) teaching profession. Yet before introducing the application into the EFL classrooms, it is no doubt imperative to discern what is preferable among EFL learners. Thus, the aim of the present study was to examine the extent to which EFL learners perceive TikTok as facilitating their learning. To this end, the participants (N = 31) were asked to fill out a short, online questionnaire to gather information about (i) whether they utilized TikTok as an affordance for their EFL learning and (ii) whether they perceive its integration into the EFL classrooms as facilitative of their learning. The findings revealed that although they did not explicitly mention that they used TikTok as an affordance for their EFL learning, they held a belief that TikTok is effective in promoting their English proficiency. According to the students, there were three factors of note which contribute to the effectiveness of TikTok, namely abundant authentic input availability, easy-to-grasp information and availability of free tuition related to English language learning. Pedagogically, it implies that TikTok is worth integrating into the EFL classrooms.